For this case we must simplify the following expression:

We must add similar terms taking into account that:
- Equal signs are added and the same sign is placed.
- Different signs are subtracted and the major sign is placed.

Thus, the simplified expression is:

Answer:

I have included a picture. In the picture you will find the work and final answer.
Answer:
Step-by-step explanation:
(x^2 +1)(x^2 +1)
x^4 +x^2+x^2 +1
x^4+2x^2 +1 answer
Hope this helps!
Answer:
B
Step-by-step explanation:
We can notice that based on the given pattern, the average rate of change from
to
, where
, is
.
So, the average rate of change from
to
is
.
Answer:
(10, 3)
Step-by-step explanation:
Solve by Substitution
2x − 4y = 8 and 7x − 3y = 61
Solve for x in the first equation.
x = 4 + 2y 7x − 3y = 61
Replace all occurrences of x with 4 + 2y in each e quation.
Replace all occurrences of x in 7x − 3y = 61 with 4 + 2y. 7 (4 + 2y) − 3y = 61
x = 4 + 2y
Simplify 7 (4 + 2y) − 3y.
28 + 11y = 61
x = 4 + 2y
Solve for y in the first equation.
Move all terms not containing y to the right side of the equation.
11y = 33
x = 4 + 2y
Divide each term by 11 and simplify.
y = 3
x = 4 + 2y
Replace all occurrences of y with 3 in each equation.
Replace all occurrences of y in x = 4 + 2y with 3. x = 4 + 2 (3)
y = 3
Simplify 4 + 2 (3).
x = 10
y = 3
The solution to the system is the complete set of ordered pairs that are valid solutions.
(10, 3)
The result can be shown in multiple forms.
Point Form:
(10, 3)
Equation Form:
x = 10, y = 3